Tracing the Flight: Investigating the Introduction of Avian Metapneumovirus (aMPV) A and B - Giovanni Franzo; Matteo Legnardi; Giulia Faustini; Riccardo Baston; Francesca Poletto; Mattia Cecchinato; Claudia Maria Tucciarone (Animals, 2024)
Avian metapneumovirus (aMPV) has been identified as an important cause of respiratory and reproductive disease, leading to significant productive losses worldwide. Different subtypes have been found to circulate in different regions, with aMPV-A and B posing a significant burden especially in the Old World, and aMPV-C in North America, albeit with limited exceptions of marginal economic relevance. Recently, both aMPV-A and aMPV-B have been reported in the U.S.; however, the route of introduction has not been investigated. In the present study, the potential importation pathways have been studied through phylogenetic and phylodynamic analyses based on a broad collection of partial attachment (G) protein sequences collected worldwide. aMPV-B circulating in the U.S. seems the descendant of Eastern Asian strains, which, in turn, are related to European ones. A likely introduction pathway mediated by wild bird migration through the Beringian crucible, where the East Asian and Pacific American flight paths intersect, appears likely and was previously reported for avian influenza. aMPV-A, on the other hand, showed a Mexican origin, involving strains related to Asian ones. Given the low likelihood of trade or illegal importation, the role of wild birds appears probable also in this case, since the region is covered by different flight paths directed in a North–South direction through America. Since the information on the role of wild birds in aMPV epidemiology is still scarce and scattered, considering the significant practical implications for the poultry industry demonstrated by recent U.S. outbreaks, further surveys on wild birds are encouraged.